Airway bacterial colonization and serum C‐reactive protein are associated with chronic obstructive pulmonary disease exacerbation following bronchoscopic lung volume reduction. (29th September 2014) - Fruchter, Oren; Rosengarten, Dror; Goldberg, Elad; Ben‐Zvi, Haim; Tor, Ruth; Kramer, Mordechai R.
Abstract: Introduction: Stable chronic obstructive pulmonary disease (COPD) patients often have lower airway bacterial colonization (ABC) which may modulate exacerbation frequency. Data regarding the association between ABC and post‐procedural COPD exacerbations following bronchoscopic lung volume reduction (BLVR) are scant. Objectives: Our aim was to explore the correlation among ABC, serum C‐reactive protein (CRP) level and the risk of COPD exacerbation within a month following BLVR. Methods: Pre‐procedure bronchoalveolar lavage (BAL) quantitative bacterial cultures and serum levels of CRP were evaluated in severe COPD patients ( N = 70, mean FEV1 = 34.6%) before BLVR by polymeric lung sealant. Results: Colonization with potential pathogenic microorganism (PPM) was observed in 40 (57.1%) patients. Out of 28 patients (40%) who had COPD exacerbation within 30 days of BLVR, 23 (82.1%) had PPM in BAL culture compared with only 14 (33.3%) out of 42 patients who had uneventful procedure ( P = 0.0027). Serum CRP level was significantly higher in patients with exacerbation compared with those with no exacerbation (mean 47.8 ± 66.0 mg/L vs 13.05 ± 27.7 mg/L, respectively, P = 0.0063). The combination of CRP level above 3.12 mg/L and PPM growth in BAL was observed in 89.2% of patients with exacerbation compared with only 52.3% of patients without exacerbation ( P = 0.0031). Conclusions: ABC is common in severe COPD patients undergoing BLVR, and along with elevated CRP level both are associated with high risk of immediate post‐procedural COPD exacerbation. These patients should be identified, carefully observed and possibly benefit from prophylactic microbiologically directed antibiotic treatment.